Between voluntarism and resistance: The Ottoman mobilization of manpower in the First World War - Beşikçi, Mehmet. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
This dissertation examines the Ottoman experience of mobilization of manpower in the First World War. By focusing mainly on Anatolia and the Muslim population, it aims to explore how the Ottoman state tried to cope with the challenges of permanent mobilization for the war effort. The dissertation also aims to analyze how this process reshaped state-society relations in Anatolia. It is argued that social actors were not passive vis-à-vis the state during the Ottoman mobilization effort: they had agency and produced responses that would reshape the mobilizing policies that targeted them. Based on how social actors’ own expectations and priorities matched up with state policies under ever-deteriorating wartime conditions, the dissertation demonstrates that these responses constituted a wide spectrum ranging from voluntary support to open resistance. In turn, the state responded by revising its mobilization policies and reformulating new mechanisms of control at the local level. The research for this dissertation is largely based on the primary sources at the Ottoman State Archives (BOA), The Turkish General Staff Military History Archives (ATASE), and the National Archives of Britain. Moreover, the relevant newspapers and journals of the period under study, and the diaries-memoirs of various people who participated in the mobilization experience also constitute a major part of the documentary basis of this dissertation.|Keywords: the First World War, mobilization, conscription, volunteers, paramilitary associations, draft-evasion, deserters, gendarmerie.
Keywords: World War, 1939-1945 -- Manpower -- Turkey.; Armed Forces -- Mobilization -- History -- 20th century.; Military service, Voluntary -- Turkey -- History -- 20th century.; Draft -- Turkey -- History -- 20th century.